Profil Fitokimia dan Aktivitas Bioaktif Temulawak (Curcuma xanthorrhiza Roxb.) Berdasarkan Kajian Literatur - Tassa Tassa; Ardi Mustakim (Lembaga Pengembangan Kinerja Dosen, 2026)
Temulawak (Curcuma xanthorrhiza Roxb.) is an indigenous medicinal plant of Indonesia that has been widely used in traditional medicine and shows considerable potential in the health and pharmaceutical fields. This potential is related to its diverse secondary metabolites with bioactive properties. This review article aims to examine the phytochemical profile of temulawak, the analytical methods used to identify bioactive compounds, and their reported biological activities based on literature studies. The method applied was a literature review of scientific articles discussing the chemical composition and biological activities of temulawak. The results indicate that temulawak contains major compounds such as curcuminoids, xanthorrhizol, flavonoids, phenolic compounds, and essential oils, which are commonly identified using chromatographic and spectroscopic techniques. Several studies report that temulawak exhibits antioxidant, anti-inflammatory, antibacterial, hepatoprotective, and potential anticancer activities. These findings indicate that temulawak has significant potential as a source of natural bioactive compounds. In conclusion, temulawak possesses a rich phytochemical profile and promising biological activities, supporting its potential application in the development of natural-based health and pharmaceutical products.